Susceptibility of Cultivated Plants to Sumatran Elephant (Elephas maximus sumatranus) in The Human Elephants Conflict Area in Aceh Province - Kaniwa Berliani; Hadi Sukadi Alikodra; Burhanuddin Masy'ud; Mirza Dikari Kusrini (Jurnal Manajemen Hutan Tropika, 2016)
Study on human-elephant conflict was conducted in Aceh Province in August 2013−April 2014 to assess susceptibility of farms by crop raiding elephants. The locations were determined by selected areas impacted by elephant conflict including Cot Girek, Mane, Meureudu, Sampoiniet, and Pantai Ceureumen.  150 respondents was interviewed to  assess the variety of the commodity plant species cultivated by local community within study areas, species of damaged commodity plants,  species of undamaged commodity plants, and the planting system. There were 29 species considered as commodity plants cultivated by farmers. Moreover, 5 commodity plants were considered as high risk plants damaged by elephant including areca, banana, oil palm, paddy, and rubber. On the other hand, species considered as low risk or undamaged consist of cacao, coffee, chili, candlenut, and patchioli. Those low risk or undemaged commodity plants species have a potential to be promoted as elephant-friendly crop commodities in area adjacent to elephant habitat based on the analysis and the categorization of susceptibility of cultivated plants against crop raiding elephant. One of the problems of human-elephant conflict is crop raiding of village farms. It is assumed that elephants might destroy a particular species therefore  information on the species could assist farmers in selecting appropriate crop to be planted.  There is a risk that current polyculture and monoculture planting system used by farmers will not prevent farms from crop raiding elephants.